An overview of treatment options for COVID-19 - Mohapatra, Madhusmita Mohanty; Rajaram, Manju; Dwivedi, Dharm Prakash; Govindraj, Vishnukant; Upadhya, Pratap (International Journal of Basic & Clinical Pharmacology, 2020)
Severe acute respiratory syndrome- coronavirus-2 (SARS-CoV-2) which emerged in Wuhan initially as pneumonia of unknown origin in December 2019, later spread to whole world and became pandemic on 11th March, 2020. Many drugs have been proposed but are backed without clinical evidence. Scientific bodies are in the row to discover a reliable vaccine and effective drugs against the novel coronavirus. Many antiviral and anti-parasitic drugs which were thought to have some effect on Coronavirus disease 2019 (COVID-19) have been tried during the crisis but none have shown concrete evidence of action. Randomized clinical trials on the repurposed drugs are now registered under clinical trial registry to look at the safety profile and efficacy of the drugs to be used against SARS-CoV-2. Many meta-analyses are being conducted worldwide to frame evidence for the fight against this novel coronavirus. We are providing below a review of various drugs that have been tried for treatment of COVID-19 as well as different clinical trials which are underway.